Fire in the fireplace charismatic renewal in the nineties - Hummel, Charles E. (Downers Grove, Il IVP, 1993)
Includes bibliographical references and indexes.
Keywords: Pentecostalism -- biblical teaching; Church history -- 20th century -- United States